Meeting Report: Vaccine Stability Considerations to Enable Rapid Development and Deployment - Mark Alasandro; Dilip Choudhury; Kim Huynh-Ba; Jianmei Kochling; Christopher Latoz; Laure Larkin; Lori McCaig; Nanda Subbarao; Yan Wu; Yajie Zhang (SpringerOpen, 2021)
Abstract The Stability Community of the American Association of Pharmaceutical Scientists (AAPS) held a virtual workshop on "Vaccine Stability Considerations to Enable Rapid Development and Deployment", on March 24-25, 2021. The workshop included distinguished speakers and panelists from across the industry, academia, regulatory agencies, as well as health care leaders. This paper presents a review of the topics covered. Specifically the challenges in accelerating vaccine development and analytical characterization techniques to establish shelf-life were covered. Additionally, vaccine stability modeling using prior knowledge stability models and advanced kinetic analysis played a key in the EUA approaches discussed during the workshop. Finally, the role of stability studies in addressing the challenges of vaccine distribution and deployment during the pandemic were a focus of presentations and panel discussions. Although the workshop did not have any presentation topics directly dedicated to the mRNA vaccines, the techniques discussed are generally applicable. The mRNA vaccine developers were represented in the panel discussions, where experts involved in the EUA approval/deployment stages for this vaccine type could discuss the challenges as applied to their vaccines.